Instructing the method of ball shooting in the practice of young basketball players - Yakovykh V.Yu.; Yakovykh Yu.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to assess the significance of ball-handling skills in the context of basketball and to explore the methods employed by coaches to teach these skills in early-stage training programs. Methods and structure of the study. The following methods were used: analysis of scientific literature, pedagogical observation, interview, analysis of competitive activity, processing of research results. We reviewed and analyzed 54 games of the 15th international club basketball tournament among professional teams from Eastern Europe of the VTB United League in the 2023/2024 season, 33 games of the 1st round of the MLBL Championship-Ural Siberia Children among young men born in 2010 and 2012. 18 coaches of youth teams participated in the interview. Results and conclusions. Over the past 10 years, technical and tactical actions in basketball have changed. The reason for this was a rule change in 2013 that limited the time for subsequent attacks after the first one to 14 seconds. The main emphasis in the attack began to be placed on players who, in case of time constraints, using complex and delicate ball handling, beat their opponents and complete the attack with an effective throw. The total average time of driving the ball in a basketball match was revealed. There are five main blocks of exercises aimed at teaching the technique of leading the ball in the groups of initial training, which are basic in the «ball school» of young basketball players.